Pradigma Baru Pelayanan Publik Indonesia Dari Old Public Adminintration Menuju New Public Service - Iskandar, Adetya; Tanjung, Elsa Susanna Fitri; Siagian, Jonathan; Tampubolon, Dominggos Soarez; Samosir, Adrilla Yolanda; Sinurat, Patrcia; Sitinjak, Ryan Fernando; Ivanna, Julia (Mahesa Research Center, 2023)
The main problem of public services today is related to improving the quality of the service itself. In terms of its implementation pattern, public services in Indonesia still have various weaknesses, such as being less responsive, less informative, less accessible, less coordinated, bureaucratic, less willing to listen to complaints / suggestions / aspirations of the public, and inefficiency. The problem that the writer will study is regarding the concept of public service implementation that has shifted from the old paradigm known as the Old Public Administration to a new paradigm known as the New Public Service. The purpose of this research is to see whether the paradigm shift finds a change in the implementation of public services in various forms or aspects of public service in Indonesia. The research methods of literature review or literature study contain theoretical theories that are relevant to research problems. In this case the public service in question must be able to build trust and collaboration with citizens, which must prioritize the principles of good governance, where public services are built based on shared values by fostering trust and collaboration with citizens.